Pemberitaan di Media Massa sebagai Pembentuk Reputasi Organisasi - Ike Devi Sulistyasningtyas (Jurnal ILMU KOMUNIKASI, 2005)
Abstract: Reputation not only about what the organization do for positive image, but it is the set of meanings by which an object is known and trough which people discribe, remember and relate to it. In practice, a lot of things shape the reputation. One of them is the mass media that used logic by itself to make symbolic words. Issues about the organization have important implication, because improving the public sensitivity which have unstable and difficult characteristic to account.